Effect of oral semaglutide on the pharmacokinetics of thyroxine after dosing of levothyroxine and the influence of co-administered tablets on the pharmacokinetics of oral semaglutide in healthy subjects: an open-label, one-sequence crossover, single-center, multiple-dose, two-part trial. (2nd September 2021) - Hauge, Camilla; Breitschaft, Astrid; Hartoft-Nielsen, Marie-Louise; Jensen, Simon; Bækdal, Tine A.
ABSTRACT: Background: Oral semaglutide comprises the glucagon-like peptide-1 analog, semaglutide, and sodium N -(8-[2-hydroxybenzoyl] amino) caprylate (SNAC). Levothyroxine has similar dosing conditions to oral semaglutide. This trial investigated if oral semaglutide co-administered with levothyroxine affects thyroxine (T4 ) exposure and if multiple placebo tablets co-administered with oral semaglutide affect semaglutide exposure. Research design and methods: In this one-sequence crossover trial, 45 healthy subjects received levothyroxine (600 μg single-dose) alone, or with concomitant SNAC 300 mg or concomitant oral semaglutide 14 mg at steady-state. Subjects also received oral semaglutide 14 mg at steady-state alone or with five placebo tablets once-daily for 5 weeks. Results: A 33% increase in total T4 exposure was observed with levothyroxine/oral semaglutide vs levothyroxine alone, but baseline-corrected maximum concentration ( C max ) was unaffected. SNAC alone did not affect total T4 exposure, whereas C max was slightly decreased. A 34% decrease in semaglutide exposure was observed when oral semaglutide was co-administered with placebo tablets, and C max also decreased. Conclusions: Levothyroxine pharmacokinetics were influenced by co-administration with oral semaglutide. Monitoring of thyroid parameters should be considered when treating patients with both oral semaglutide and levothyroxine. Oral semaglutide exposure was influenced by co-administration with multiple tablets, which is addressed in the dosing guidance.